Implementation of Habitation Activities in Forming Students' Religious Character at Senori Islamic High School Tuban - Karnoto, Kacung Al; Syafi’i, Imam (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2025)
Education has a strategic role in ensuring the survival of the nation and state, especially as the main means of improving the quality of human resources. Periodic curriculum changes are made to adapt education to the development of information technology and the dynamics of the modern era. One important aspect of education is religious education, which functions as a guide in forming a meaningful, peaceful, and dignified life. Islamic Religious Education (PAI) aims to develop the spiritual potential of students, form individuals who believe and are devoted to God Almighty and have noble morals. Religious education also aims to produce people who are honest, fair, have good character, are disciplined, and respect each other. This study aims to explore and analyze the implementation of habituation activities in forming the religious character of students at SMA Islamiyah Senori. A qualitative approach with a case study method is used to gain an in-depth understanding. Data were collected through direct observation, in-depth interviews with PAI teachers, students, and school staff, and analysis of relevant documents. The focus of the study lies in religious habituation activities that are carried out routinely and in a structured manner. The results of the study indicate that the implementation of habituation activities at SMA Islamiyah Senori is carried out through programs such as congregational prayer, reading the Qur'an, religious lectures, and memorization. These programs are designed to internalize religious values ​​in the daily lives of students. The implementation of these habituation activities has proven effective in forming religious character, as indicated by increased obedience to worship, discipline, honesty, and a sense of responsibility of students. The success of this program is supported by the strong commitment of all school residents, active support from parents, and a school environment that is conducive to religious activities. However, the study also found several obstacles, such as limited time for program implementation, lack of supporting facilities, and diverse religious backgrounds of students. These obstacles require special attention to ensure that the program runs optimally. This study concludes that habituation activities at SMA Islamiyah Senori have an important role in forming the religious character of students. As a recommendation, this study suggests strengthening cooperation between schools and parents, providing adequate supporting facilities, and developing habituation programs that are more innovative and relevant to the needs of students. The findings of this study are expected to be a reference for other schools in developing similar programs that are oriented towards forming the religious character of students.